N6-Methyladenosine Guides mRNA Alternative Translation during Integrated Stress Response - Zhou, Jun; Wan, Ji; Shu, Xin Erica; Mao, Yuanhui; Liu, Xiao-Min; Yuan, Xin; Zhang, Xingqian; Hess, Martin E.; Brüning, Jens C.; Qian, Shu-Bing (Molecular cell, 2018)
The integrated stress response (ISR) facilitates cellular adaptation to stress conditions via the common target eIF2α. During ISR, the selective translation of stress-related mRNAs often relies on alternative mechanisms, such as leaky scanning or reinitiation, but the underlying mechanism remains incompletely understood. Here we report that, in response to amino acid starvation, the reinitiation of ATF4 is not only governed by the eIF2α signaling pathway, but is also subjected to regulation by mRNA methylation in the form of N6-methyladenosine (m6A). While depleting m6A demethylases represses ATF4 reinitiation, knocking down m6A methyltransferases promotes ATF4 translation. We demonstrate that m6A in the 5′ UTR controls ribosome scanning and subsequent start codon selection. Global profiling of initiating ribosomes reveals widespread alternative translation events influenced by dynamic mRNA methylation. Consistently, Fto transgenic mice manifest enhanced ATF4 expression, highlighting the critical role of m6A in translational regulation of ISR at cellular and organismal levels. [Display omitted] •ATF4 reinitiation involves the m6A demethylase ALKBH5•ATF4 reinitiation is sensitive to mRNA m6A levels•Global alternative translation is modulated by 5′ UTR m6A levels•Liver-specific FTO transgenic mice show altered translation initiation Zhou et al. show that amino acid starvation-induced ATF4 translation is subject to regulation by mRNA methylation in the form of m6A. Global analysis of translation initiation reveals that m6A in the 5′ UTR modulates start codon selection, thereby controlling alternative translation.